A study on impact of social media on student's academic performance in UiTM Merbok, Kedah / Amani Hanina Abd Rahman And Anis Nur Atiqa Jana - Abd Rahman, Amani Hanina; Atiqa Jana, Anis Nur (2017)
Social media are a collection of internet websites, service and practices that help collaboration, community building, participation and sharing information (Junco.Heiberger and Loken, 2010 ). A major category of social media activity is called social networking (Junco,Heiberger and Loken, 201 0; Junco and Mastrodicasa,2007). The use of social networking sites has been widespread through the world (Banquil et. al, 2009). Currently, there are dozens of social networking websites available online,each with its own special something to offer its members (Hudson Horizons, 2011 ), but Facebook, Twitter, MySpace and Linkedln have become the most visited social networking sites in the world (Haridakis and Hanson, 2009). Among these face book is the most popular social networking site. In 2009, it has more than 350 million users (Kirschner and Karpinski, 2010).